Penerapan Metode Pembelajaran Kolaboratif dalam Memahami Karya Sastra Hindu di Kalangan Mahasiswa - Putriyani, Ni Luh PT. Putriyani Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Understanding Hindu literary works often faces various challenges, mainly due to the complexity of language, text structure, and historical context. This study aims to analyze the effectiveness of collaborative learning methods in enhancing students' comprehension of Hindu literature. Using a qualitative approach and a case study method, this research involved 12 students divided into four groups. Data were collected through interviews, observations, and document analysis of students' discussion results. The findings indicate that the collaborative learning method significantly improves students' comprehension, increasing from 30% before implementation to 80% afterward. The main benefits gained by students include enhanced understanding, critical thinking skills, and improved communication abilities. However, challenges such as differences in students' comprehension levels, lack of teamwork skills, and time management issues were identified. To address these challenges, proposed strategies include the active role of lecturers as facilitators, task distribution within groups, better time management, and the integration of blended learning. This study is expected to serve as an innovative learning model for understanding Hindu literature and contribute to preserving the cultural values embedded within it.